Studies of Li2Fe0.9M0.1SO Antiperovskite Materials for Lithium–Ion Batteries: The Role of Partial Fe2+ to M2+ Substitution - Gorbunov, Mikhail V.; Carocci, Salvatore; Gonzalez Martinez, Ignacio G.; Baran, Volodymyr; Mikhailova, Daria (Frontiers in Energy Research, 2021)
ABSTRACT Cubic Li2Fe0.9M0.1SO antiperovskites with M - Co2+ or Mn2+ were successfully synthesized by a solid-state technique, and studied as cathode materials in Li-batteries. The influence of the Co and Mn cation substitution of Fe in Li2FeSO on the resulting electrochemical performance was evaluated by galvanostatic cycling, while the reaction mechanism was explored by applying operando X-ray absorption and X-ray diffraction techniques using synchrotron radiation facilities. Even 10% Fe-substitution by these metals completely changes the structural behavior of the material upon Li-removal and insertion, in comparison to Li2FeSO. The Co-substitution significantly improves cyclability of the material at high current densities in comparison to the non-substituted material, reaching a specific capacity of 250 mAh/g at 1C current density. In contrast, the Mn-substitution leads to deterioration of the electrochemical performance because of the impeded kinetics, which may be caused by the appearance of a second isostructural phase due to formation of Jahn-Teller Mn3+ cations upon delithiation.